Glycosaminoglycans From Plant Sources and The Potential Uses as Anticoagulant and Anticancer Agents (Journal of Biochemistry, Microbiology and Biotechnology, 2019)
Glycosaminoglycans (GAGs) are usually found in mammals or invertebrates organisms. Since there are many potential active ingredients in plants that have not been investigated till dates, this review will be discussing the plants’ potential to be the alternative for GAGs source. The study will enlighten the correlation between two crucial properties, anticoagulant and anticancer properties. This is because these two properties are usually found in organisms with GAGs presence. GAGs have obviously played an important role to elicit these two properties within an organism’s biological system. The study found that based on previous researches investigations, plants have the potential to have GAGs which then act as replacement of anticoagulant carrying anticancer properties.
Keywords: Glycosaminoglycans; medicinal plants; anticancer; anticoagulant